96: Serum Levels of Soluble FAS and Soluble FAS Ligand in Pregnant Women Who Smoke. Issue 6 (1st June 2014) - Nair, V; Hasan, SU; Yusuf, K
Abstract: BACKGROUND: Cigarette smoking during pregnancy is associated with adverse pregnancy outcomes. Paradoxically, women who smoke during pregnancy have a reduced risk of preeclampsia (PE). Placentas of women with PE show higher levels of trophoblast apoptosis. Both Fas and Fas ligand belong to the tumor necrosis factor family of proteins and the Fas-Fas ligand system, also known as the death factor system, is one of the main pathways for apoptosis. Higher levels of soluble Fas (sFas) have been reported in PE. OBJECTIVES: To determine levels of sFas and soluble Fas Ligand (sFasL) in pregnant women who smoke. DESIGN/METHODS: Using enzyme linked immunosorbent assay (ELISA), we prospectively analyzed serum levels of sFas and sFasL in normotensive mothers who smoke and normotensive non-smoking mothers. Exclusion criteria include chronic hypertension, autoimmune disorders, rupture of membranes, evidence of labour and history of drug use. Statistical analysis was performed using a two-way non-paired Student t test or the Mann-Whitney U test as appropriate.Using enzyme linked immunosorbent assay (ELISA), we prospectively analyzed serum levels of sFas and sFasL in normotensive mothers who smoke and normotensive non-smoking mothers. Exclusion criteria include chronic hypertension, autoimmune disorders, rupture of membranes, evidence of labour and history of drug use. Statistical analysis was performed using a two-way non-paired Student t test or the Mann-Whitney U test as appropriate. RESULTS: The median maternal age in smoking mothers was lower as compared to normotensive nonsmoking mothers. The median gestational age was 31 weeks in both the groups. Levels of sFasL were significantly higher in smoking group compared to normotensive non-smoking group (37 pg/mL* vs. 12.14 pg/mL; P<0.0001). sFas did not differ between the two groups. CONCLUSIONS: We found higher levels of sFasL in normtensive smoking mothers. We speculate that higher sFasL may explain the reduced incidence of PE in pregnant mothers who smoke by binding to the elevated sFas levels in pregnant mothers who may otherwise go on to develop PE.